Technological change and agrarian structure : a study of Bangladesh - Ahmed, Iftikhar; Cline, William (fwd.) (Geneva, 1981)
This study on rural Bangladesh reveals that the inverse relationship between farm size and over-all land productivity ob served in a traditional agricultural setting is weakened or eliminated following the introduction of Green Revolution techno logy. The effects that a prevailing tenurial system has on productivity and employ ment in the cultivation of traditional and high-yielding variety (HYV) crops appear to vary. In some instances share-cropping depresses output and labour use; in others it has no significant effect. Reliance on small-scale family farms permits a more intensive use of labour accompanied by higher levels of farm output (traditional crops) or at the very least not involving a sacrifice of crop output (HYV). The smaller farms tend to cultivate (and double-crop) a higher percentage of their land with HYVS than do larger farms. In the context of a high and rising level of landlessness, the determinants of the demand for hired labour are examined in this study in rela tion to both agrarian structure and technological change. The study also presents concrete quantitative evidence on the existence and manifestation of rural factor market imperfections which provides valuable policy insights for improving the access of the rural poor to key agricultural inputs, working capital and government extension services. The study examines in depth the effectiveness of communication channels in the dissemination of knowl edge on new technologies, and concludes that farmers, particularly smaller ones, rely on indigenous systems rather than change agents and mass media. Using logit and multiple regression analysis, the study also investigates the relationship between the diffusion of technology and a range of institutional parameters. The val idity of the issues discussed, the methodo logy and analytical framework applied and the empirical findings and conclusions put forward in the study goes far beyond the limits of this case study alone.
Keywords: Land reorm - Bangladesh